Theoretical investigation of the quasi-ring C-H...π interactions / Lee Sin Ang ... [et al.] - Ang, Lee Sin; Ab Ghani, Zaidi; Yaakob, Mohd Hafiz; Mohamed Ibrahim, Mohamed Ismail (Universiti Teknologi MARA, 2021)
The quasi-ring C-H...π interactions have been reported to be responsible for the stability of crystalline materials. The statistical analysis, together with electronic structure calculations in the framework of density functional theory and Moller-Plesset have also provided positive data on the aforementioned interactions. However, improvements can be had in the theoretical calculations, where the basis set convergence is not explored. This is crucial as the interactions are of weak type, reported to be around 4 - 5 kcal mol-1. In this investigation, the idea is to combine the geometry, potential energy surface, and bonding analysis to provide different insights into the interactions. Our results show that the original configurations of the crystals, even with the substitutions of linear chains, are more favorable than the rotated ones. Further calculations are needed to verify the involvements of the π orbitals of the N, C, Cl, S and the d-orbital of Cu, and the s-orbital of hydrogen atoms.